Value of pretreatment automated hemogram as a 5-year survival predictor in uterine cervical cancer clinical stage IIB-IVA - Luna-Abanto, Luciana Isabel (2021)
Objetive: To identify the value of the automated pretreatment blood count as a predictor of actuarial survival and 5-year disease-free actuarial survival in patients with clinical stage IIB-IVA cervical cancer. Material and Methods: Analysis of survival that evaluated 48 patients with pathologic diagnosis of clinical stage IIB-IVA cervical cancer treated with chemoradiotherapy treated at the Medical Oncology service at the Virgen de la Puerta High Complexity Hospital during the period 2015-2017. Results: The mean age of the patients was 51.78 ± 12.06 years (Range: 32-77 years). The average tumor size was 5.55 ± 1.33 cm (Range: 3 - 9 cm). Regarding the clinical stage according to the FIGO classification, it was found that 77.7% was classified as stage IIB, 20.8% as IIIB and 2.1% had a diagnosis of stage IVA cervical cancer. Univariate analysis found that anemia, leukocytosis, thrombocytosis, neutrophil / lymphocyte index, neutrophilia, and high platelet / lymphocyte index are not predictors of 5-year actuarial survival (p> 0.05), in terms of disease-free survival at 5 years it was found that anemia, leukocytosis and pretreatment neutrophil / lymphocyte index showed a trend towards significance (p = 0.05-0.1) and pretreatment neutrophilia is a predictor of 5-year disease-free survival, being statistically significant (0% vs 38.9%, p = 0.026). Conclusion: Pretreatment neutrophilia (> 7,500 μL) is a prognostic factor for 5-year disease-free survival in patients with clinical stage IIB-IVA cervical cancer undergoing chemoradiotherapy